The Illuminated Brand: Patrick White's The Vivisector - Kikot, Edward Mark (My University, 1986)
Through the written word, whether in the form of novel, short story, memoir, or letter, Patrick White has struggled to apprehend the experiential "Word", which is the ineffable name for God. The cabalistic focus of this calling has forced the author, both as poet and as artist, to wrestle with the angel of- his personal religious faith in many different guises and from many points of view, thereby creating the personas of a host of characters. As a result, he has developed a well-rounded vision of the human condition, at the centre of which may be seen, by those men and women initiated through suffering and love, the invisible-green burning bush of a profound spiritual life.
In addressing this concern, central to all of White's work, I have attempted to exprore the-precise nature and relevance of the religious experience as illuminated by the contemplative, apophatic "light" of the Christian mystical tradition, and as that "light", emerging out of darkness, corresponds to the creative spirit's sense of revelation. This study is composed of three parts. The introduction concentrates on White's personal religious bias qualified by Thomas Merton's belief and analysis of man's "fundamental religious instinct". The section entitled "Preliminaries" constitutes a brief survey of White's novels in so far as they help to substantiate the basic premise of my thesis. The third and final chapter examines in-depth The Vivisector, the role of the artist in relation to his art which reflects his relation with his God.
Keywords: English Language and Literature; English Language and Literature